2022
DOI: 10.3390/ijerph192316045
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Nonlinear and Threshold Effects of Travel Distance on the Travel Mode Choice across Different Groups: An Empirical Study of Guiyang, China

Abstract: Examining how travel distance is associated with travel mode choice is essential for understanding traveler travel patterns and the potential mechanisms of behavioral changes. Although existing studies have explored the effect of travel distance on travel mode choice, most overlook their non-linear relationship and the heterogeneity between groups. In this study, the correlation between travel distance and travel mode choice is explored by applying the random forest model based on resident travel survey data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Furthermore, this study emphasized the relevance of trip purposes in shaping transport preferences. The results showed that the preference for PMVs increases with longer travel distances, likely due to their convenience and comfort [22,55]. Additionally, women tended to choose PMVs over AMs more often.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, this study emphasized the relevance of trip purposes in shaping transport preferences. The results showed that the preference for PMVs increases with longer travel distances, likely due to their convenience and comfort [22,55]. Additionally, women tended to choose PMVs over AMs more often.…”
Section: Discussionmentioning
confidence: 92%
“…The recorded transport modes also yield valuable information about individuals' specific transport choices, encompassing PMV, PT, or AM options. The distances traveled, and data on personal preferences, attitudes, education, occupation, and per capita income provide a comprehensive understanding of how socio-demographic and trip variables influence modal selection, offering a holistic view of their overall perception of sustainable transport options [55][56][57].…”
Section: Data Collectionmentioning
confidence: 99%